INHIBITORY ACTIVITY OF BIOACTIVE COMPOUNDS OF Spirulina platensis COMBINED WITH CINNAMALDEHYDE AGAINTS DNA GYRASE: SINGLE AND MULTI-LIGAND DOCKING - Deaniar Hafilah; Heli Siti Halimatul Munawaroh; Siti Aisyah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Antibiotic resistance poses a serious challenge in treating bacterial infections, necessitating the development of new antibacterial alternatives. Spirulina platensis and cinnamon oil, rich in bioactive compounds, have demonstrated antibacterial potential in vitro, although their molecular mechanisms remain largely unexplored. This research aims to evaluate the interactions of several bioactive compounds derived from Spirulina platensis combined with cinnamaldehyde against DNA gyrase, a critical bacterial enzyme, using molecular docking approach. Single and multi-ligand approaches were employed to analyze binding affinity, inhibition constants (Ki), and molecular interactions, including hydrogen bonding and hydrophobic interactions. Docking validation demonstrated high accuracy with an RMSD value of 0.680 Å. Single ligands yielded binding affinities ranging from -6.1 to -7.7 kcal/mol. Multi-ligand combinations significantly enhanced antibacterial activity, with the six-ligand combination showing the most promising results, displaying the lowest binding energy (-19.02 kcal/mol) supported by six hydrogen bonds. Visualization confirmed ligand interactions with the same active site on DNA gyrase, involving critical residues such as ASN54, ASP81, ILE86, SER55, GLY85, GLY125, GLU58, THR173, ARG84, and PRO87. These findings reveal the synergistic effects of multi-ligand interactions that can improve complex stability and antibacterial activity. The study supports the development of natural compound combinations as an effective alternative in addressing antibiotic resistance.